The Legislation of Labour Relations in Canada Post - Wright, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper situates the events surrounding the passing of the Postal Services Continuation Actin a social, political and historical context. The significance of the back-to-work legislation is discussed and the problems it présents for laborer are analyzed.